Stylizacja tonów tajskich za pomocą Prosogramu - Włodarczak, Marcin (Investigationes Linguisticae, 2006)
The aim of this study is to establish whether stylisation of F0 contours based on d'Alessandro and Mertens's model of tonal perception can be successfully applied to lexical tones of Central Thai. The percentage of correct responses to the manipulated stimuli was found to be significantly lower than the results for natural tones reported in literature on the subject.